ACTIVE METHODOLOGIES IN THE DEVELOPMENT OF BNCC COMPETENCIES: AN INTEGRATIVE REVIEW - Garajau , Naiara Cristina de Souza; Santos, Adalayne Lisboa; de Araujo , Alessandra Cristina; da Silva, Altaide Pereira; de Oliveira, Caroline Quadros; dos Santos, Emerson Oliveira; Caria, Josiano Régis; Faraco , Paulo Ricardo; Araújo, Susana de Sousa; Moura , Vinícius da Silva Ferreira (Editora Impacto Científico, 2025)
This study aimed to analyze the contributions of active methodologies to the development of the competencies established by the Brazilian National Common Curricular Base (BNCC) through an integrative literature review. The methodology consisted of a systematized search in the SciELO, ERIC, CAPES Periodicals and institutional repositories, covering the period from 2015 to 2025, with the application of previously defined inclusion and exclusion criteria. Seventeen studies were selected to compose the final sample. The data obtained showed that strategies such as project-based learning, flipped classroom and problem-based learning promote student protagonism, intellectual autonomy and active participation, in addition to contributing significantly to the development of cognitive, socio-emotional, communicative and collaborative competencies provided for in the BNCC. It was also found that the articulation between active methodologies and the pedagogical use of digital technologies expands the possibilities for personalizing learning and respecting different learning paces and styles. Thus, it is understood that active methodologies constitute a consistent pedagogical contribution to the implementation of a competency-based curriculum, although challenges related to continuous teacher education, curricular organization and institutional conditions still persist, which reinforces the need for further empirical research on the topic. DOI: https://doi.org/10.56238/edimpacto2025.092-054